2001
DOI: 10.1007/s002640000216
|View full text |Cite
|
Sign up to set email alerts
|

Kashin-Beck disease and iodine deficiency in Tibet

Abstract: We evaluated iodine and selenium status in 575 children between 5 and 15 years with Kashin-Beck disease from endemic and non-endemic areas. Of these 267 (46%) children had goiter. The proportion of subjects with goiter was higher in the villages with Kashin-Beck disease than in the control village. In the villages with Kashin-Beck disease, 105 (23%) of the subjects had a serum thyrotropin greater than 10 mU/l as compared with 3 (4%) in the control village. The percentages of low serum thyroxine values and low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 10 publications
0
34
0
Order By: Relevance
“…A significant prevalence of goitre exists in Tibet. An appropriate dietary programme of iodine and selenium supplements should be encouraged [11,12,16]. The bilateral nature of the symptoms seen in 79% of the cases on a clinical basis [9,10] is even more evident on radiological examination where 99.4% of the lesions are bilateral.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant prevalence of goitre exists in Tibet. An appropriate dietary programme of iodine and selenium supplements should be encouraged [11,12,16]. The bilateral nature of the symptoms seen in 79% of the cases on a clinical basis [9,10] is even more evident on radiological examination where 99.4% of the lesions are bilateral.…”
Section: Discussionmentioning
confidence: 99%
“…This sum gives a scale from 0 to 36. This scale is divided into four stages: stage 0, I (1-10), II (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and III (21-36). The bilateral presence of radiological signs was tested for each variable with the κ-test.…”
Section: Methodsmentioning
confidence: 99%
“…However, no favorable effects have been reported for progression of clinical conditions in HIV-infected patients [82], neonatal outcomes in very low birth weights infants [83], adult asthma [84], thyroid function in pregnant women from a mild-to-moderate iodine-deficient population [85] and Hashimoto thyroidits [86], postnatal depression [87], and rheumatoid arthritis [88]. On the contrary, weak indications of positive effects of Se have been given by a randomized trial on critically ill patients [89] and a trial for the prevention of an osteoarthropathy named Kashin-Beck disease [90,91], the association of which with Se status is uncertain [92]. Beneficial effect of Se has been noted for disease progression in the case of patients with mild Graves' orbitopathy [93], pre-eclampsia and pregnancy-induced hypertension [94], and for some outcomes of patients critically ill, specifically, with septic syndrome [95,96].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Selenium deficiency in humans can therefore interact critically in I metabolism, leading to an I-unresponsive condition or, even worse, a negative response to I (Hotz et al, 1997). Some recent reports have suggested that Kashin-Beck disease might also be related to I deficiencies as well as Se deficiency (Moreno-Reyes et al, 2001;Zhang et al, 2001). Given the fact that in many parts of China Se and I deficiencies occur together (Tan, 1989), it is necessary to consider a possible dual supplementation of the two elements in the diet.…”
Section: Introductionmentioning
confidence: 99%